Kojak : Season One Disc 5 - Mann, Abby, 1927-2008.; Savalas, Telly (USA Universal TV, 1973)
Lt. Theo Kojak is the main character in this popular television police drama. Kojak is a tough cop, but his trademark is a fondness for lollipops. Despite his difficult work, he tirelessly brings criminals to justice while staying upbeat and good-natured.
A balding New York City detective cop, Lt. Theo Kojak, is primarily best-known for his no-nonsense capacity of bringing criminals and sending them to justice, in a calmly and quietly matter. He also had the knack of licking lollipops and using his popular catch-phrase, "Who Loves Ya, Baby?" At work in the New York Precinct, prior to loading up several cases on the scene of the crime, he frequently supports and often had a close bond with each of his workers, Det. Dan Frazer, Det. Bobby Crocker (with whom he always admired, all the time), and Det. Stavros (A.K.A. "Demosthenes").
Language : English Subtitles : No Subtitles
Keywords: Crime; Drama; Mystery -- Tv Series